Effect of alirocumab added to high-Intensity statin therapy on endothelial function in patients with acute myocardial infarction: a sub-study of the randomized placebo-controlled PACMAN-AMI trial. (3rd October 2022) - Rexhaj, E; Soria, R; Baer, S; Kavaliauskaite, R; Yasushi, U; Tatsuhiko, O; Temperli, F; Shibutani, H; Siontis Cm, G; Haener D, J; Stortecky, S; Windecker, S; et al.
Abstract: Background: Endothelial dysfunction is involved early in the development of vascular dysfunction leading to atherosclerosis and cardiovascular diseases. Statins have shown to improve endothelial function. The role of the protein convertase subtilisin/kexin type 9-inhibitor (PCSK9) alirocumab on endothelial function among patients with acute myocardial infarction (AMI) remains unknown. Purpose: We investigated the effect of alirocumab on endothelial function among AMI patients receiving PCSK9i alirocumab in addition to high intensity statin therapy. Methods: This is a pre-specified, sub-study nested within the PACMAN-AMI (effects of the PCSK9 antibody AliroCuMab on coronary Atherosclerosis in patieNts with Acute Myocardial Infarction) trial, a randomized trial that compared the effects of biweekly PCSK9-inhibitor alirocumab 150 mg vs. placebo, initiated within 24h of presentation in patients with AMI on top of high-intensity statin. Patients recruited at Bern University Hospital and adherent to the study drug (alirocumab or placebo) were analysed for the current study. Endothelial function was assessed by flow mediated dilation (FMD) of the brachial artery at week 4 and 52 after treatment initiation. Results: Among 139 patients (68 alirocumab, 71 placebo) completing the sub-study, baseline characteristics were well balanced between groups (alirocumab vs. placebo: mean age 57.5±10.1 years vs. 58.7±8.4 years, p=0.45; mean LDL-C 4.03±0.93 mmol/L vs. 4.05±0.74 mmol/L, p=NS). At week 52 LDL-C levels decreased to 0.65±0.71 mmol/L in the alirocumab group and to 1.98±0.71 mmol/L in the placebo group (p<0.001). There was no difference in FMD at 52 weeks in the alirocumab (5.44±2.24%) versus placebo (5.45±2.19%) group (between groups difference FMD, −0.21% (95% CI −077 to 0.35), p=0.47). Compared to baseline, follow-up FMD was improved in both groups (from 4.52±1.87 to 5.44±2.24%, p<0.001 in the alirocumab group and from 4.32±1.62 to 5.45±2.19%, p<0.001 in the placebo group). Conclusion: Among patients with acute myocardial infarction, the addition of subcutaneous biweekly alirocumab, compared with placebo, to high-intensity statin therapy did not result in additional improvement of endothelial function after 52 weeks of treatment. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): The PACMAN-AMI study was supported by a research grant from Sanofi, Regeneron and Infraredx. This substudy was funded by the University of Bern.